Etnicidade e literatura: a presença do negro na literatura marginal periférica - Mongim, Luciana Marquesini (2019)
This thesis focuses on the critical reading of Elizandra Souza's Águas da Cabaça (2012) poetry book and Allan da Rosa's Reza de Mãe (2016), as a way of analyzing aesthetic strategies and resources poetic-discursive that structure the writing of two peripheral marginal authors of São Paulo, in which they relate literature, ethnicity, cultural identity and territory. The works integrate a network of dialogues and displacements of meanings that relates to the African Diaspora, the strategies of resistance, negotiation and elaboration of the identities of Afrodescendants and the cultural aspects and everyday experiences of the black being in the contemporary urban periphery. They delineate the black and peripheral body that transits in the urban space, as well as discursive and identity productions that dialogue with different codes and supports and that cause ruptures in the literary and linguistic canon and deconstruct stereotyped and discriminatory images, structuring a peripheral afro-marginal poetics. The procedure of analyzing the works is based on the comparative method of poetical dictions and the aesthetic elaborations of writers, as a way of highlighting the unfolding of the AfroDiaspora and Afro-Descendant aesthetics in contemporary peripheral marginal literary production. The approximations and differences between the writers base the singularities inherent to them in the process of construction of their poetic making and the black and peripheral body that is transposed in written handwriting. The analysis is based on the theoretical elaborations on cultural identity and its relations with ethnicity and the black diaspora, formulated by Stuart Hall (2003), and the reflections on black political and cultural history in the West, developed by Paul Gilroy (2001). Feminist criticism, especially related to black feminism, like the theoretical postulates of Djamila Ribeiro, Conceição Evaristo, Carla Aktirene, Joice Berth, Lélia Gonzales, Sueli Carneiro, bell hooks, Angela Davis, Patricia Hill Collins, Judith Buttler, Kimberlé Crenshaw, support the problematization of intersectionalities and the feminine, black and peripheral poetic subject in the process of elaborating a feminine identity in the periphery. Still grounding the discussion on oppressive factors that intersect, the notion of urban territory, which assumes the centrality of enunciation and statement, is taken from the geographical studies developed by Milton Santos, Rogério Haesbaert and Carlos Walter Porto-Gonçalves.